2022
DOI: 10.3390/nano12213851
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Degradation of Selected Toxic Dyes by Green Biosynthesized Silver Nanoparticles Using Aqueous Leaf Extract of Cestrum nocturnum L.

Abstract: In the present study, the catalytic degradation of selected toxic dyes (methylene blue, 4-nitrophenol, 4-nitroaniline, and congo red) using biosynthesized green silver nanoparticles (AgNPs) of Cestrum nocturnum L. was successfully performed. These AgNPs are efficiently synthesized when a reaction mixture containing 5 mL of aqueous extract (3%) and 100 mL of silver nitrate (1 mM) is exposed under sunlight for 5 min. The synthesis of AgNPs was confirmed based on the change in the color of the reaction mixture fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These observations reflect the role of nanoparticles as substrates due to their high specific surface area [ 77 , 78 ]. For silver nanoparticles, several studies have demonstrated enhanced catalytic behavior for dye degradation with NaBH 4 [ 79 , 80 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…These observations reflect the role of nanoparticles as substrates due to their high specific surface area [ 77 , 78 ]. For silver nanoparticles, several studies have demonstrated enhanced catalytic behavior for dye degradation with NaBH 4 [ 79 , 80 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specific compounds from the plant extract act as reducing agents and facilitate the rapid and effective degradation of the dyes. This study highlights the promising potential of photoinduced AgNPs as efficient catalysts for dye degradation, offering new insights into their mechanism of action and potential applications in environmental remediation [55].…”
Section: -Nitrophenolmentioning
confidence: 89%
“…Efficient synthesis of AgNPs was achieved by exposing a reaction mixture containing 5 ml of 3% aqueous extract of Cestrum nocturnum leaf and 100 ml of 1 mM silver nitrate to sunlight for 5 min according to [55]. The confirmation of AgNPs synthesis was based on the observed change in the color of the reaction mixture, from pale yellow to dark brown, with the maximum absorbance recorded at 455 nm.…”
Section: -Nitrophenolmentioning
confidence: 99%
“…In this scenario, metal nanoparticles play an important role in the decolorization of organic dyes and in the presence of reducing agent NaBH 4 can accelerate electron transfer during the reduction reactions. [17][18][19] In heterogeneous catalysis processes, control of nanoparticle morphology contributes a major role in catalytic efficiency. A number of nanoparticles (Au, Ag, Cu, Fe etc.)…”
Section: Introductionmentioning
confidence: 99%